Peri-operative antibiotic usage during endourological surgery: A multi-institutional, national-level, cross-sectional audit of prevalent practice pattern in India - Rishi Nayyar; Shritosh Kumar; Collaborative Working Group on Use of Antibiotics in Endourology (Indian Journal of Urology, 2023)
Introduction: Antibiotic use during endourological procedures is often discordant from the reported guidelines, despite the potential risks of antibiotic resistance, adverse effects, and health-care costs. A nationwide audit was conducted, with the support of the Urological Society of India, to ascertain the current antibiotic prescription practices for the endourological procedures and the reasons associated with them. Methods: A multi-institutional, national-level, cross-sectional audit analyzing elective endourological procedures was performed. The data regarding the disease profile; risk factors for infectious complications; urine culture; pre-, per-, and post-operative antibiotic use; additional antibiotic use; and patient demographics were collected in a standardized pro forma. Reasons for prescribing antibiotics divergent from the guideline recommendations were also noted. Any infectious complication that necessitated the antibiotic use was also noted prospectively up to 1 month. All the data were entered into a single centralized and customized online portal on a real-time basis. Results: One thousand five hundred and thirty-eight cases were recruited from 20 hospitals. A single-dose prophylaxis was prescribed in only 319 (20.7%) of the cases, and the majority received a multi-day prophylaxis. A combination of two or more antibiotics was prescribed as the prophylaxis in 51% of the cases. One thousand three hundred and fifty-six (88.2%) cases were continued on a long-duration prophylaxis after the discharge, with 1191 (77.4%) receiving it for > 3 days. One thousand one hundred and sixty (75.4%) cases received a guideline-discordant prophylaxis solely on the basis of the surgeon's or institution's protocol, rather than any specific case based need. Ninety eight (6.4%) cases developed postoperative urinary tract infection. Conclusions: Multi-dose, combination and post-discharge antibiotic prophylaxis for endourological surgeries is highly prevalent in India. This audit highlights the huge potential to reduce such guideline-discordant overuse of antibiotics during the endourological procedures.